2021
DOI: 10.1016/j.isci.2021.103185
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 integral membrane proteins shape the serological responses of patients with COVID-19

Abstract: SARS-CoV-2 pandemic has elicited a unique mobilization of the scientific community to develop efficient tools to understand and combat infection. Like other coronavirae , SARS-CoV-2 hijacks host cell secretory machinery to produce viral proteins that compose the nascent virions; including Spike (S), Envelope (E) and Membrane (M) proteins, the most exposed transmembrane proteins to the host immune system. As antibody response is part of the anti-viral immune arsenal, we investigate the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…We observed that the mutation in D614 has a high risk related to antibody-binding and can reduce the recognition capability by targeting antibodies to the S-glycoprotein. The outcome of our in silico risk analysis study of D614G corroborates the previous experimental study’s result by Martin et al [ 72 ]. Their study has found that the D614G mutation decreased antibody binding of the S-glycoprotein.…”
Section: Discussionsupporting
confidence: 92%
“…We observed that the mutation in D614 has a high risk related to antibody-binding and can reduce the recognition capability by targeting antibodies to the S-glycoprotein. The outcome of our in silico risk analysis study of D614G corroborates the previous experimental study’s result by Martin et al [ 72 ]. Their study has found that the D614G mutation decreased antibody binding of the S-glycoprotein.…”
Section: Discussionsupporting
confidence: 92%
“…One study has investigated clinical outcome associations of IgM responses to whole proteins in a mammalian cell-based assay, where the membrane is presumed to be presented in a similar fashion as on virions: exposing only the M1 epitope. Consistent with our findings, membrane protein specific IgM was associated with severe disease, although that method is unable to resolve the spike binding to the epitope level and so the unusual isotype pattern and strength of the IgM responses of the membrane epitope relative to other single epitopes is less apparent (71).…”
Section: Discussionsupporting
confidence: 88%
“…1, S2). The N-terminus (amino acids [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and C-terminus (amino acids [205][206][207][208][209][210][211][212][213][214][215][216][217][218][219][220][221][222] are not resolved in the map and were not modeled. Loops connecting transmembrane helices (amino acids 36-42 and 71-78) are the least well resolved regions of the structure.…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, the M protein sequence has remained virtually unchanged-a testament to the critical role that M plays in viral replication and assembly 35 . Furthermore, while only 20 amino acids in length, the N-terminus of M has been found to be highly immunogenic in COVID-19 patients [8][9][10][11] . M has also been shown to modulate innate immune response and could contribute to lung injury often seen in severe cases 25,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation